Effectiveness of Green Space in Improving Mental Health: A Review (International Journal of Built Environment and Sustainability, 2025)
Increasing urbanisation throughout the world has increased the number of mental health cases in citizens, especially in metropolitan areas. Various studies have conveyed the positive linkage between increased green space exposure in the daily life of urban citizens and mental health improvement. However, the current state of knowledge has limited information on percentage of effectiveness of green spaces in improving mental health. Apart from that, the contributions of green space attributes that enhance the improvement of mental health remains unclear. Thus, this study aims to discover the percentage of efficiency of green spaces in improving mental health through systematic review and meta-analysis. The formula for calculating confidence interval of odds ratio is used to calculate the standard error of each study and the random effect inverse-variance approach was used in the meta-analysis to identify the combined effect of the studies. Results from meta-analysis indicated that green spaces can provide an average of 17% [OR (95%CI): 0.83 (0.78–0.88)] improvement in the mental health of a person in terms of stress, depression, and anxiety. Apart from that, green space effectiveness in improving mental health varies with the influence of attributes such as bigger size, better accessibility, and higher tree density. The findings of this review provide evidence that green space exposure can improve the mental health of urban citizens. This study is significant to government bodies and developers as a guideline to implement more green spaces in urban areas that are filled with dense buildings. Overall, this review provides insights on social benefits of green space in improving mental health of citizens, indicating that green space that is accessible, big and has high density of greenness can be beneficial for urban citizen’s mental health.
Keywords: Urban Green Space, Greenness, Mental Health, Psychological Distress, Meta Analysis